Sustainable development in circular agriculture: An illustrative bee↺legume↺poultry example. (25th October 2022) - Rauw, Wendy M.; Gomez‐Raya, Luis; Star, Laura; Øverland, Margareth; Delezie, Evelyne; Grivins, Mikelis; Hamann, Karen T.; Pietropaoli, Marco; Klaassen, Michiel T.; Klemetsdal, Gunnar; Gil, María G.; Torres, Olga; et al.
Abstract: Circular economic principals of production are based on material flows through the system with minimum external inputs, recycling of resources, generating minimum waste, emissions, or pollution. Agriculture presents a major opportunity for the utilization of wastes, by‐products and co‐products in the development of a circular economy via the design of circular agricultural production systems and the creation of new sustainable value chains. The present work outlines an illustrative example of a circular bee↺legume↺poultry agricultural production system, based on the premise that: (1) there is an urgent need to prioritize pollinator stewardship and pollinator ecosystem restoration to counteract pollinator decline, (2) the EU Plant Protein Plan fosters EU‐grown plant proteins including local legumes, and (3) poultry production is the most important segment of the animal production industry, and the fastest growing agricultural sub‐sector. For the successful implementation of circular agriculture, multidisciplinary research is needed regarding all sectors involved, as well as practical evaluations and the realization of proof of concept depending on the geographical location. For sustainable circular agricultural practices to be adopted by agriculturists and agricultural workers, a culture shift is needed, with close cooperation between all actors involved.